Preferences for self-care or professional advice for minor illness: a discrete choice experiment - Porteous, Terry (Oxford University Press, 2006)
AIM: To determine the relative importance of factors that influence decision making in the management of minor illness, and how people trade between these factors. DESIGN OF STUDY: Discrete choice experiment. SETTING: Scottish electoral roll. METHOD: Six hundred and fifty-two responders of a previous national survey were invited to complete a discrete choice experiment questionnaire. This was used to measure relative preferences for managing symptoms of minor illness often associated with analgesic use. Three attributes were identified as important to participants: type of management, availability, and cost of managing symptoms. Trade-offs between these attributes were examined. RESULTS: A 57% response rate was achieved (51% valid response rate). People preferred to manage symptoms by self-care and were willing to pay almost £23 to do so. Community pharmacy was the preferred source of advice. Responders preferred less waiting time and paying less money when managing symptoms, and were willing to trade between factors. A less preferred type of management became more attractive when waiting times and cost were reduced. CONCLUSION: Findings suggest that self-care is the preferred method of managing symptoms of minor illness. When developing services to support self-care, policy makers should invest in services that reduce waiting times and incur least cost to users.